Tres coyunturas historiográficas y Don Medardo Mejía: una aproximación - Euraque, Darío (2016)
This article locates the historical work of Don Medardo Mejia within the general framework of the historiographical evolution of Honduras in the 20th century. We argue that Don Medardo wrote history that should be linked to one of three historiographical junctures that, in our opinion, c1early demarcate la representation of Honduras's past in the 20th century. The three junctures are included in the following chronological structure: 1926- 1954 ,with the command of philosophical eclecticism from the Honduran Academy of Geography and History, of which Don Medardo distanced himself. After this first delimitation was another between 1955 and 1977 ,to which Don Medardo belonged. Here, Don Medardo was a pioneer in introducing social sciences as a key instrument in historical explanation. Following this was a third historiographical juncture between 1978 and 2000, at its height in the Department of History at the National Autonomous University of Honduras (UNAH), already at the end of Don Medardo's most productive years.